The Influence of Visual Appeal on Trust Mediated by Presence and Authenticity in Shopee Live Users - Anissa Pranadewi; Anas Hidayat (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of visual appeal on trust with the mediating role of presence and authenticity in Shopee Live users. This study uses a quantitative approach with a survey method of 292 respondents who are active users of Shopee Live in Yogyakarta, who have exceeded the minimum number of samples required in the PLS-SEM analysis. The sampling technique used non-probability sampling using the convenience sampling method, and the data analysis was carried out using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results of the study show that visual appeal has a positive effect on presence and authenticity. Furthermore, presence and authenticity have a positive effect on trust, and presence also affects authenticity. In addition, presence and authenticity have been shown to mediate the relationship between visual appeal and trust, both partially and sequentially. These findings suggest that visual appeal not only increases trust directly, but also through psychological mechanisms such as a sense of presence and perception of authenticity.